2003
DOI: 10.1021/ja035018z
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Inhibitor for Fe-type Nitrile Hydratase:  2-Cyano-2-propyl Hydroperoxide

Abstract: Nitrile hydratase (NHase) is a non-heme iron or non-corrin cobalt enzyme having two post-translationally modified ligand residues, cysteine-sulfinic acid (alphaCys112-SO(2)H) and -sulfenic acid (alphaCys114-SOH). We studied the interaction between Fe-type NHase and isobutyronitrile (iso-BN) which had been reported as a competitive inhibitor with a K(i) value of 5 microM. From detailed kinetic studies of the inhibitory effect of iso-BN on Fe-type NHase, we found that authentic iso-BN was hydrated normally and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 60 publications
3
54
0
Order By: Relevance
“…Considering these findings, we would like to propose that the oxygen atoms in the oxidized cysteine residues are derived from water molecules, although the oxygen atoms in the cysteine residues modified through oxidation using an inhibitor (2-cyano-2-propyl hydroperoxide) for Fe-NHase and spontaneous oxidation are proposed to come from water molecules (41) and dissolved oxygen (34), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Considering these findings, we would like to propose that the oxygen atoms in the oxidized cysteine residues are derived from water molecules, although the oxygen atoms in the cysteine residues modified through oxidation using an inhibitor (2-cyano-2-propyl hydroperoxide) for Fe-NHase and spontaneous oxidation are proposed to come from water molecules (41) and dissolved oxygen (34), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidation of the equatorial Cys residues is required for catalytic activity. 10,11 Even though the structures of Fe-and Co-type NHases are very similar, Fe-type NHases are specific for Fe(III), whereas Co-type NHases are specific for Co (III). 8 Several open reading frames have been identified just downstream from the structural α-and β-subunit genes in NHases, and one of these genes has been proposed to function as an activator protein ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the αH80A/αH81A and αH80W/αH81W mutant enzymes exhibited a blueshift along with an increase in molar absorptivity (Table S2). The observed red-shifts in this LMCT band are typically observed when (i) the pH is increased, (ii), upon interaction with an inhibitor such as butyric acid, (iii), changes in hydrogen-bonding at or near the active site or (iv) oxidation of αCys-SOH to αCys-SO2H 1,36,37 On the other hand, blue-shifts are observed by the addition of substrate and also upon disruption of the hydrogen-bonding network between βArg56 and accessed by following the link in the citation at the bottom of the page. Vol 20, No.…”
Section: Resultsmentioning
confidence: 94%
“…Several studies on both Fe-and Co-Type NHases have shown the importance of the stability and integrity of the Cys-SOH ligand for catalytic activity in NHases; for example, further oxidation to Cys-SO2H leads to inactivation. 27,37 Most recently, in our studies with the Co-Type NHase from P. thermophila JCM 3095, we showed that Cys-SOH can function as a nucleophile in the hydration of nitrile to amides by NHase. 12 Therefore stabilization of αCys 104 -SOH in CtNHase through hydrogenbond formation with αR157 is important for a fully functional NHase enzyme.…”
Section: Discussionmentioning
confidence: 93%